PENGARUH KEPEMIMPINAN SUPERVISOR TERHADAP KINERJA KARYAWAN HOUSEKEEPING DEPARTMENT DI HOTEL PANGERAN BEACH PADANG - Rahmansyah, Jeffry; Yuliana, Yuliana; Meirina, Ira (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of research is to determine the effects of leadership on employee performance Housekeeping department at Pangeran Beach Hotel Padang. This research is research that is associative causal. The population in the study amounted to 34 people. The sampling technique using total sampling, all members of the population defined as a sample. Data collection for the variables supervisor leadership is done by using a questionnaire by using a Likert scale that has been tested for validity and reliability. While the data for performance variables are taken from the housekeeping department employee performance reports in 2016. Based on the results showed that the leadership has a positive and significant influence on employee performance. This is indicated by the value of 3.746 > ttable 2.036 and significant level of 0.001 < 0.05. So there is a significant positive effect between leadership (X) on employee performance (Y).Keywords: Leadership, Supervisor, Performance, Housekeeping department